Characterization of in vitro dengue virus resistance to carrageenan - Talarico, Laura Beatriz (2016)
The λ-carrageenan (λ-car) is a potent and selective inhibitor of dengue virus (DENV) infection targeted to virus adsorption and internalization, due to the structural similarities with the mammalian cell receptor heparan sulfate. To further characterize the antiviral activity of λ-car, the selection and the phenotypic and genomic features of λ-car resistant DENV-2 variants are studied here in comparison to control virus. Resistant variants were rapidly selected in Vero cells after three passages in presence of the drug. No difference was detected in the growth profiles in Vero and C6/36 cells between resistant and control viruses. By contrast, the kinetics of adsorption and internalization of resistant variants in Vero cells was significantly diminished whereas entry to C6/36 cells was unaffected. By plaque purification and sequence analysis of the population, two types of resistant clones were found: some clones presented two mutations in E protein, K126E, and F422L; but other equally λ-car resistant clones had no mutations in E. Furthermore, no mutations were found in other viral proteins like prM, C, or NS1. The genomic disparity in E protein was also associated to differences in phenotype stability. The stable genomic resistance here described provides information about determinants in E protein involved in receptor binding and membrane fusion for uncoating.